Clinical profile and Outcome of patients of Heart Failure with and without Chronic Kidney Disease - Subedi, Manoj; Chhetri, Roshan; Uranw, Surendra; Sharma, Sanjib Kumar (Journal of Advances in Internal Medicine, 2024)
BACKGROUND Heart failure is a leading cause of mortality globally. Chronic Kidney Disease is one of the major co-morbidity that is associated with higher morbidity and mortality in Heart failure. Clinical profile and data on outcome of Heart failure patients with Chronic Kidney Disease are limited. METHODS In this prospective observational study; we enrolled 200 patients of Heart failure from November 2018 to October 2019 and later they were stratified into two groups as Heart failure with and without Chronic Kidney Disease. Their clinical profile, risk factors, laboratory parameters and echocardiography were compared. Patients were followed up after a period of 3 months and their outcome was analyzed. RESULTS The mean age of patient was 64.7±14.9 years in Heart failure with Chronic Kidney Disease and 60±16.4 years among those without Chronic Kidney Disease (p value=0.08). Heart failure patients with Chronic Kidney Disease were more likely to present with orthopnea/Paroxysmal nocturnal dyspnea and bilateral lower limb swelling ( p value <0.05).. Heart failure patients with Chronic Kidney Disease had higher blood pressure, more likely to have anemia and albuminuria at presentation (p value=<0.05). The mortality of HF patients with Chronic Kidney Disease and probable Chronic Kidney Disease at 3 months was 34% and 15% in remaining group (p value=0.002). CONCULSIONS Heart failure patients with Chronic Kidney Disease are older, have more comorbidity, more orthopneic and edematous at presentation and are less likely to receive optimal medical therapy. 3 month mortality was significantly higher in those with renal dysfunction.